2014
DOI: 10.1002/cphc.201402392
|View full text |Cite
|
Sign up to set email alerts
|

Selective Extraction of Metal Ions from Aqueous Phase to Ionic Liquids: A Novel Thermodynamic Approach to Separations

Abstract: The selective extraction of metals from aqueous mixtures has generally relied on the use of selective ionophores. We present an alternative strategy that exploits a recently developed approach to extraction into an ionic liquid phase, and show that a high degree of control over selectivity can be obtained by tuning the relative concentrations of extraction agents. A thermodynamic model for the approach is presented, and an experimental separation of strontium and potassium ions is performed. It is shown that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The observed anion:copper ratios do not necessarily indicate that the anions are coordinated with the copper, as previous work indicates that charged metal complexes are soluble in ILs [14,15] and uncoordinated ions can move into the IL phase in tandem with a charged metal complex to maintain electroneutrality [59,60]. As indicated in Table 3, all three mineral anions used in the present study coordinate relatively weakly with copper(II).…”
Section: Extractions Involving a Single Copper Saltmentioning
confidence: 52%
See 1 more Smart Citation
“…The observed anion:copper ratios do not necessarily indicate that the anions are coordinated with the copper, as previous work indicates that charged metal complexes are soluble in ILs [14,15] and uncoordinated ions can move into the IL phase in tandem with a charged metal complex to maintain electroneutrality [59,60]. As indicated in Table 3, all three mineral anions used in the present study coordinate relatively weakly with copper(II).…”
Section: Extractions Involving a Single Copper Saltmentioning
confidence: 52%
“…Ion exchange mechanisms involving metals and IL cations have been studied extensively [55][56][57][58][59][60], and it is observed that strongly hydrophobic cations such as 1-decyl-3-methylimidazolium generally do not undergo extensive ion exchange [61]. The trialkylammonium species in the ILs used in the current study are sufficiently hydrophobic that it would be quite surprising if they engaged in ion exchange to a significant degree.…”
Section: Mechanism Of Extractionmentioning
confidence: 93%
“…Although not examined experimentally in this work, the literature on electrodeposition of metals from anhydrous ILs [23][24][25][26] suggests that this should be a general phenomenon. More particularly, if this approach should be developed into a technology, we would use cation-selective ILs [27][28][29][30][31][32][33]…”
Section: Discussionmentioning
confidence: 99%
“…An excellent discussion on the topic of metal extraction to ILs is available in the literature by Janssen et al [111] The experimental works of Dietz et al, [117,118] Jensen et al, [119,120] Visser et al, [121,122] and Janssen et al [123,124] definitely deserve attention and can provide a profound insight on the mechanistic processes, while a thermodynamic perspective on the topic has been provided by Kobrak. [125] A detailed discussion of all mechanistic considerations is not within the scope of the present review; thus, we strongly encourage the readers to refer to the works cited above to get a deeper understanding of the quite complicated but very interesting topic of extraction mechanisms.…”
Section: Extraction Mechanisms Of Metals To Ionic Liquidsmentioning
confidence: 99%
“…An excellent discussion on the topic of metal extraction to ILs is available in the literature by Janssen et al [111] . The experimental works of Dietz et al., [117,118] Jensen et al., [119,120] Visser et al., [121,122] and Janssen et al [123,124] . definitely deserve attention and can provide a profound insight on the mechanistic processes, while a thermodynamic perspective on the topic has been provided by Kobrak [125] .…”
Section: Ionic Liquids In Liquid–liquid Separationsmentioning
confidence: 99%